Climate change affects winter chill for temperate fruit and nut trees - Luedeling, Eike; Girvetz, Evan Hartunian; Semenov, Mikhail A.; Brown, P.H. (Public Library of Science, 2011)
Temperate fruit and nut trees require adequate winter chill to produce economically viable yields. Global warming has the potential to reduce available winter chill and greatly impact crop yields.